A study on relationship of Plasmids with Azithromycin and Ciprofloxacin Resistance in isolates causing Urinary Tract Infection - Zaima, Faizah (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.